Penerapan Teori Behaviorisme Dalam mengatasi Dampak Negatif Gadget pada Tingkah Laku Anak Usia Dini di TK Insan Madani - Tri Hariyati; Maftukhah, Nurul; Dhea Putri Sakilla (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Based on the results of research that I found on this behaviorism method, it can be concluded that the negative effects of the absence of control in playing gadgets will cause changes in children's behavior into tantrums. The purpose of this study to determine the negative impact of gadgets on early childhood behavior. This study uses a descriptive qualitative research method with Ajo research subject a student of diTK Insan Madani who experienced negative changes in behavior. Based on the results of research that I found, it can be concluded that the negative effects of the absence of control in playing gadgets will cause changes in children's behavior into tantrums. After being given action, Ajo showed a significant improvement in his behavior. That is, Ajo already wants to postpone his competition to play gadgets and do other positive activities. Conclusion the application of Behaviorism method can overcome the negative impact of gadgets on early childhood behavior in TK Insan Madani. Parents at home are expected to always supervise all children's activities, especially when playing gadgets because it can affect children's behavior to be negative, namely tantrums. And it is expected for teachers to do parenting to parents or guardians of students to continue to collaborate to improve the intelligence and behavior of children to continue to be better for a glorious future.